2006
DOI: 10.1086/499218
|View full text |Cite
|
Sign up to set email alerts
|

Iron Depletion in the Hot Bubbles in Planetary Nebulae

Abstract: We have searched for the emission from [Fe X]λ6374 and [Fe XIV]λ5303 that is expected from the gas emitting in diffuse X-rays in BD+30 • 3639, NGC 6543, NGC 7009, and NGC 7027. Neither line was detected in any object. Models that fit the X-ray spectra of these objects indicate that the [Fe X]λ6374 emission should be below our detection thresholds, but the predicted [Fe XIV]λ5303 emission exceeds our observed upper limits (one sigma) by factors of at least 3.5 to 12. The best explanation for the absence of [Fe … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…In our previous paper (Georgiev et al 2006b), we showed that the X-ray-emitting plasma in NGC 6543 is heavily depleted in iron. This chemical peculiarity allows one to determine the origin of this plasma by comparison with the iron abundances in the stellar wind and the nebular gas.…”
Section: Comparison Of the Abundances In The Stellar Wind And The X-rmentioning
confidence: 84%
See 3 more Smart Citations
“…In our previous paper (Georgiev et al 2006b), we showed that the X-ray-emitting plasma in NGC 6543 is heavily depleted in iron. This chemical peculiarity allows one to determine the origin of this plasma by comparison with the iron abundances in the stellar wind and the nebular gas.…”
Section: Comparison Of the Abundances In The Stellar Wind And The X-rmentioning
confidence: 84%
“…They concluded that the iron forest in the UV is reproduced with an iron content equal to 1/4 of the solar value, but they cannot rule out the solar composition either. Previously, we have found the X-ray-emitting plasma to be depleted in iron by a factor of 8 (Georgiev et al 2006b). This result again implies that the hot gas arises from nebular material rather than from the stellar wind.…”
Section: Comparison Of the Abundances In The Stellar Wind And The X-rmentioning
confidence: 91%
See 2 more Smart Citations
“…For the time being, the existing observations do not seem to be consistent with such a limb brightening. Georgiev et al (2008) found recently that the wind of the central star of NGC 6543 is less depleted in iron compared to the plasma emitting the diffuse X-rays (Georgiev et al 2006). They concluded that the X-ray emitting plasma "is derived from nebular gas rather than the stellar wind".…”
Section: Discussionmentioning
confidence: 99%